Effect of probiotic intake on athletic ability in healthy people: a systematic review and Bayesian meta-analysis - Zhang, Xuda; Chang, Zhizhao; Zhao, Shiao; Wu, Xinfan; Wang, Xianfei; Ai, Guowen; Ning, Ziheng (Frontiers in Nutrition, 2026)
IntroductionTo address ongoing debate about whether probiotic supplements enhance athletic performance in healthy individuals, and amid uncertainty about effective doses, strain formulations, and population-specific responses, we conducted a prospectively registered systematic review and Bayesian multi-level meta-analysis of randomized controlled trials in healthy adults.MethodsWe searched six databases from inception to 1 July 2025. Two reviewers independently completed study selection, data extraction, and risk of bias assessment using ROB. We synthesized data using hierarchical Bayesian models, and evaluated publication bias with funnel plots, Egger’s test, and significance-based diagnostics.ResultsTwenty-one trials (N = 685) were included. Probiotic supplementation was associated with a small-to-moderate improvement in overall athletic performance [μSMD 0.38, 95% CrI 0.17 to 0.60], with the clearest gains in endurance-centric outcomes, including aerobic endurance [μSMD 0.74, 95% CrI 0.39 to 1.10] and cycle-based VO₂max [μSMD 2.21, 95% CrI 0.64 to 3.68]. Both single-strain [μSMD 0.33, 95% CrI 0.04 to 0.62] and multi-strain [μSMD 0.45, 95% CrI 0.12 to 0.79] regimens were effective. By dose, only the medium tier (1×10⁹ to 1×10¹¹ CFU per day) yielded a significant effect [μSMD 0.38, 95% CrI 0.14 to 0.62]. Significant benefits were observed in athletes [μSMD 0.38, 95% CrI 0.08 to 0.69] and in adults [μSMD 0.46, 95% CrI 0.11 to 0.81]. At the strain level, Lactobacillus plantarum showed a significant effect [μSMD 0.82, 95% CrI 0.12 to 1.50].DiscussionProbiotic supplementation is associated with a modest yet practically meaningful improvement in athletic performance among healthy adults, with benefits across single- and multi-strain products and the most consistent signal at a medium daily dose. Large multicenter trials with harmonized outcome measures are warranted to refine strain- and dose-specific recommendations. This study was registered with PROSPERO (CRD420251139260).Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251139260https://www.crd.york.ac.uk/PROSPERO/view/CRD420251139260, PROSPERO (CRD420251139260).